Formation of Consumer Impulsive Buying in MSMEs through Online Shopping Activities - Febriany, Dessy; Tjipto, Jovita Damayanti; Immanuel, Sandy; Buana, Salsabilla Ayundha Marthsa; Emerald, Serena; Keni, Keni (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Electronic commerce that continues to grow has created a fairly tight competition between business actors. However, this competition can help the sustainability of MSMEs in formulating strategies and switching to selling their products online. Various strategies can be used in e-commerce, one of which is the flash sale countdown timer program. Social media activities and flash sales promotions were able to boost sales figures after the product launch. MSME actors who enter the world of e-commerce also interact with potential buyers by holding live streaming with the aim of utilizing technological developments to reach consumers more broadly. Thus, being able to bring changes to consumer habits, they prefer to shop from home because it is easy, practical, and there are many attractive promos. Therefore, this study was made with the aim of examining the relationship between flash sale countdown timer, live streaming e-commerce on the formation of impulsive buying which is strengthened or weakened by the presence of in-home shopping tendency. Hypothesis testing is done by analyzing Partial Least Square – Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results showed that flash sale countdown timer and live streaming e-commerce had a positive effect on impulsive buying, also in home shopping tendency as a moderating variable has a positive effect.